Advances in the study of AIE polymers - Pei, Yiran; Liu, Leixin; Cao, Xinfeng; Zhou, Jian; Liu, Cuiyun (Frontiers in Materials, 2024)
Aggregation-induced emission (AIE) can exhibit different properties in different situations, such as non-emission and highly fluorescent in the dissolved state of the molecule and in the aggregate or solid state, respectively. This property of AIE is distinguished from aggregation-induced quenching (ACQ) or even the opposite. Combining the AIE phenomenon with different polymers yields different polymers with corresponding AIE properties. In this paper, the mechanism, synthesis, branching and application of AIE in the fields of optoelectronic functional materials, sensors, biology, and environment are reviewed. It is hoped that this review will stimulate more research on molecular aggregates and promote further cross-fertilisation and greater development in the disciplines of materials, chemistry and biomedicine.